Uplifting School Leadership and the Townsend/Adams Seven Powers: A Study of Leadership Growth in a Small Rural Primary School in New South Wales, Australia (Alberta Journal of Educational Research, 2021)
This article presents a rich account of school leadership development within the North Coast Initiative for School Improvement program in New South Wales, Australia. The focus is the school leader at a small rural school, whose engagement with generative dialogue and collaborative inquiry results in a growing confidence in engaging her school community. The study demonstrates the power of narrative as a mode of inquiry and leadership development as represented in the school leader’s own account of her changing relationship with her school and her developing sense of professionalism. The study evaluates the success of the approach against a model of Seven Powers derived from the work of David Townsend and Pam Adams in Alberta, Canada, that includes the positive effects of carefully constructed and managed teams, professional relationships and processes, and the use of inquiry, reflection, collaboration, modelling and narrative in supporting the professional development of a school-based leader.Key words: school leadership growth; collaborative inquiry; emotional intelligence; narrative; generative dialogue; North Coast Initiative for School ImprovementCet article présente un compte rendu riche du développement du leadership scolaire dans le cadre du programme North Coast Initiative for Schola Improvement en Nouvelle-Galles du Sud, Australie. L'accent est mis sur le leader scolaire d'une petite école rurale, dont l'engagement dans le dialogue génératif et l'enquête collaborative se traduit par une confiance croissante dans l'engagement de sa communauté scolaire. L'étude démontre le pouvoir du récit en tant que mode d'enquête et de développement du leadership, tel qu'il est représenté dans le témoignage de la directrice de l'école sur l'évolution de sa relation avec son école et le développement de son sens du professionnalisme. L'étude évalue le succès de l'approche par rapport à un modèle des Sept Pouvoirs dérivé du travail de David Townsend et Pam Adams en Alberta, Canada, qui comprend les effets positifs d'équipes soigneusement construites et gérées, de relations et de processus professionnels, et l'utilisation de l'enquête, de la réflexion, de la collaboration, de la modélisation et du récit pour soutenir le développement professionnel d'un leader scolaire.Mots clés : leadership scolaire, enquête collaborative, intelligence émotionnelle, récit, dialogue génératif, North Coast Initiative for School Improvement